2015
DOI: 10.1094/mpmi-07-14-0225-r
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Influenced Gene Expression in the Rice Endophyte Burkholderia kururiensis M130

Abstract: Burkholderia kururiensis M130 is one of the few rice endophytic diazotrophic bacteria identified thus far which is able to enhance growth of rice. To date, very little is known of how strain M130 and other endophytes enter and colonize plants. Here, we identified genes of strain M130 that are differentially regulated in the presence of rice plant extract. A genetic screening of a promoter probe transposon mutant genome bank and RNAseq analysis were performed. The screening of 10,100 insertions of the genomic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 58 publications
3
55
1
5
Order By: Relevance
“…The fact that genetic evidence has proven many of these features to be essential in reductionist systems highlights the power of linking environmental and model system approaches. Functional genomic analyses on differential gene expression aided in identifying candidate genes as well; outside the root, bacteria appear to be primed for infection, as some colonization-related genes are already induced in the presence of exudates (96) or plant extracts (30).…”
Section: Into the Roots: Ways Endophytes Get Inmentioning
confidence: 99%
“…The fact that genetic evidence has proven many of these features to be essential in reductionist systems highlights the power of linking environmental and model system approaches. Functional genomic analyses on differential gene expression aided in identifying candidate genes as well; outside the root, bacteria appear to be primed for infection, as some colonization-related genes are already induced in the presence of exudates (96) or plant extracts (30).…”
Section: Into the Roots: Ways Endophytes Get Inmentioning
confidence: 99%
“…It has been observed that residing within plant tissues offer better communication opportunities than residing in the exospheric regions. Bacterial endophytes offer more benefits and are able to interact with the host in variable environmental conditions as well [2,3]. They enhance growth of plant by direct or indirect mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Although Götz-Rösch et al (2015) believe that the bacterial AHL molecule might positively influence plant growth, evidence is lacking. However, plant-influenced gene expression in the rice endophyte Burkholderia kururiensis M130 was reported (Coutinho et al, 2015). Captivatingly, these AHL-mimicking molecules specifically alter the QS-regulated biofilm formation of two plant microbes, Sinorhizobium fredii and Pantoea ananatis , suggesting that plants can enhance or inhibit bacterial QS systems depending on the bacterial strain (Perez-Montano et al, 2013).…”
Section: Interkingdom Signalingmentioning
confidence: 99%